Antibacterial effect of Allium sativum cloves and Zingiber officinale rhizomes against multiple-drug resistant clinical pathogens - Karuppiah, Ponmurugan (Asian Pacific Tropical Medicine Press, 2012)
OBJECTIVE: To evaluate the antibacterial properties of Allium sativum (garlic) cloves and Zingiber officinale (ginger) rhizomes against multi-drug resistant clinical pathogens causing nosocomial infection. METHODS: The cloves of garlic and rhizomes of ginger were extracted with 95% (v/v) ethanol. The ethanolic extracts were subjected to antibacterial sensitivity test against clinical pathogens. RESULTS: Anti-bacterial potentials of the extracts of two crude garlic cloves and ginger rhizomes were tested against five gram negative and two gram positive multi-drug resistant bacteria isolates. All the bacterial isolates were susceptible to crude extracts of both plants extracts. Except Enterobacter sp. and Klebsiella sp., all other isolates were susceptible when subjected to ethanolic extracts of garlic and ginger. The highest inhibition zone was observed with garlic (19.45 mm) against Pseudomonas aeruginosa (P. aeruginosa). The minimal inhibitory concentration was as low as 67.00 µg/mL against P. aeruginosa. CONCLUSIONS: Natural spices of garlic and ginger possess effective anti-bacterial activity against multi-drug clinical pathogens and can be used for prevention of drug resistant microbial diseases and further evaluation is necessary.